Hopes and reality: consumers’ purchase intention towards whitening cream - Md. Monirul Islam (SpringerOpen, 2021)
Abstract In contemporary Bangladeshi society, popularity, marriage, and status are weighed on a scale where the vital criterion is a fair complexion. Women are encouraged to use whitening cream in its colour-conscious culture. The present study identifies the factors that influence consumers’ purchase intention towards whitening cream. A structured questionnaire was used to elicit feedback from 275 female respondents using the convenience sampling method. Structural equation modelling and hypotheses tests were conducted to validate the model after verifying the scale items’ reliability and validity. The findings revealed that attitude, involvement, and descriptive norms were significant factors, and injunctive norms, perceived quality, and price fairness were inessential factors in explaining Bangladeshi female consumers’ purchase intention. The framework used in the study can assist in product design. The study makes an important contribution to the literature by explaining why female consumers equate whiteness with beauty. Marketers should not use deceptive advertisements to influence them falsely; they should fulfil their expectations without causing harm or inciting racism.